-36=2v+2(v-4)

Simple and best practice solution for -36=2v+2(v-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -36=2v+2(v-4) equation:


Simplifying
-36 = 2v + 2(v + -4)

Reorder the terms:
-36 = 2v + 2(-4 + v)
-36 = 2v + (-4 * 2 + v * 2)
-36 = 2v + (-8 + 2v)

Reorder the terms:
-36 = -8 + 2v + 2v

Combine like terms: 2v + 2v = 4v
-36 = -8 + 4v

Solving
-36 = -8 + 4v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-4v' to each side of the equation.
-36 + -4v = -8 + 4v + -4v

Combine like terms: 4v + -4v = 0
-36 + -4v = -8 + 0
-36 + -4v = -8

Add '36' to each side of the equation.
-36 + 36 + -4v = -8 + 36

Combine like terms: -36 + 36 = 0
0 + -4v = -8 + 36
-4v = -8 + 36

Combine like terms: -8 + 36 = 28
-4v = 28

Divide each side by '-4'.
v = -7

Simplifying
v = -7

See similar equations:

| -7X+2+X=-16 | | 16x+4=5x-6x | | 2x+2y-2y= | | 3y-y+5y-(-2y)=-108 | | 2=-4(2x-9)+6x | | 16=X+8+2 | | (0.5x-4)-(1.5x+2.3)= | | 19x-8=12x-43 | | 12(4+n)+5(-2n-9)=1 | | 5a+8-4=-21 | | 116=-4x+2(-5x-5) | | 12x^2-96x+0=0 | | 13x=-7x+6*5 | | 110+.60x=70+.80x | | 4xy^3*7x^2y^3= | | 3(-4-2)-7=-85 | | 5+12=2z | | 17=9x+5-x | | x=60+0.50*125 | | 5x-mx=w | | 5x-7=1x-4 | | 2x/5-4=7x-8 | | 12x^2-96x=0 | | -3f+3(-3f+5)= | | -3-21x=-8x-8 | | 64-32x=80 | | 55=6a-7 | | 2xy+2x=55 | | 7x^2+4x-40=0 | | .5x+1.8=-.7 | | 6a-12=42+5z | | 2sec^2x=3tan^2x+1 |

Equations solver categories